Curatorial dreams : critics imagine exhibitions - Butler, Shelley (McGill-Queen's University Press, 2016)
Introduction:Curatorial Dreaming /Shelley Ruth Butler and Erica Lehrer --Making Transparency Visible: Centre William Rappard, Headquarters of the World Trade Organization, Geneva /George E. Marcus --Most Disturbing Souvenirs: Curative Museology in a Cultural Conflict Zone /Erica Lehrer --The Alchemy of Flight: Race, Mobility, Humanity /Chandra D. Bhimull --By and For Children: History and Healing in a Hospital Museum, KwaZulu-Natal /Monica Eileen Patterson --Frozen World/Mundo Congelado: AIDS, Chicano Art, and the Queer Remains of Mundo Meza /Robb Hernández --The Play: Reassembling African Arts in the West /Joshua I. Cohen --But Is It Art?: Not Really /Matti Bunzl --Intervention/Resurrection: Intergenerational Activations of La Cueca Sola /Lissette Olivares and Lucian Gomoll --The Terrible Gift: Difficult Memories for the Twenty-First Century /Roger I. Simon --Reading the World: Native Histories at the Bosque Redondo Memorial, New Mexico /Margaret A. Lindauer --The World in One City: The Tropenmuseum, Amsterdam /Serena Iervolino and Richard Sandell --Museum without Walls: After Into the Heart of Africa /Shelley Ruth Butler --abNormal: Bodies in Medicine and Culture /Manon Parry --Reel Objects: Movies in Museums /Janice Baker --Afterword /Barbara Kirshenblatt-Gimblett.